Volume 2: Integrity and Corrosion; Offshore Issues; Pipeline Automation and Measurement; Rotating Equipment 2000
DOI: 10.1115/ipc2000-237
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Two-Phase Flows in Pipe-Riser Systems

Abstract: A differential-algebraic system is presented to model unstable two-phase flows in pipe-riser systems. Equations derive from the space integration of an isothermal drift-flux model assuming quasi-equilibrium momentum balance. A linear analysis of this system gives a new stability criterion for gas-liquid flows in pipe-riser systems. This criterion is validated by laboratory experiments. Then, a nonlinear analysis shows that the severe slugging phenomenon is a hydrodynamic instability coming from a supercritical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…An approach based on the dynamic DAE models of the system is presented in Zakarian (2000). The approach is based on a fixed geometry of a pipe and riser, where a criterion for the stability of the system is derived based on linear analysis.…”
Section: Slug Modelling and Predictionmentioning
confidence: 99%
“…An approach based on the dynamic DAE models of the system is presented in Zakarian (2000). The approach is based on a fixed geometry of a pipe and riser, where a criterion for the stability of the system is derived based on linear analysis.…”
Section: Slug Modelling and Predictionmentioning
confidence: 99%
“…The main concern associated with slugging is that it causes the level of production to decrease. The mechanisms of these losses, corresponding to a bifurcation behavior first described in Zakarian [2000], are schematically summarized by Figure 1, where the level of production is plotted against the opening of the outlet valve for a slugging well. For high values of the opening, the production periodically oscillates in time.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, some of the parameters of the model need to be carefully tuned, in order 1 Similarly, Bøe [2] and Taitel [19] derived, from force balance equations expressed on the body of one slug, conditions on the superficial velocities of gas and liquid to predict whether a given system will experience slugging or not. Much later, these criteria were proved to correspond to a Hopf bifurcation by Zakarian [20], who analyzed a simpler DAE model and showed that, when varying certain parameters, the stability properties of the system switch at a certain critical (bifurcation) point. 2 Unfortunately, they fail to predict the instability of some systems (e.g.…”
Section: Introductionmentioning
confidence: 99%